Retribution as hierarchy regulation: Hierarchy preferences moderate the effect of offender socioeconomic status on support for retribution. (17th September 2017) - Redford, Liz; Ratliff, Kate A.
Abstract : People punish others for various reasons, including deterring future crime, incapacitating the offender, and retribution, or payback. The current research focuses on retribution, testing whether support for retribution is motivated by the desire to maintain social hierarchies. If so, then the retributive tendencies of hierarchy enhancers or hierarchy attenuators should depend on whether offenders are relatively lower or higher in status, respectively. Three studies showed that hierarchy attenuators were more retributive against high‐status offenders than for low‐status offenders, that hierarchy enhancers showed a stronger orientation towards retributive justice, and that relationship was stronger for low‐status, rather than high‐status, criminal offenders. These findings clarify the purpose and function of retributive punishment. They also reveal how hierarchy‐regulating motives underlie retribution, motives which, if allowed to influence judgements, may contribute to biased or ineffective justice systems.